2020
DOI: 10.1364/oe.387648
|View full text |Cite
|
Sign up to set email alerts
|

Averaging speckle patterns to improve the robustness of compressive multimode fiber imaging against fiber bend

Abstract: Fiber bend is a major challenge of multimode fiber (MMF) imaging. More robustness against fiber bend is demonstrated in compressive MMF imaging using mean speckle patterns captured at multiple potential bending configurations beforehand, rather than sticking to single patterns at initial configuration. Experiments demonstrate an overall quality improvement on recovered images than previous work, which is important for robust endoscopic application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…By calculating the correct series of input fields, this focused beam can be scanned over an object with a field of view defined by the numerical aperture of the fiber. The second class of methods consists of speckle imaging approaches [14][15][16][17] . With these methods, a set of speckle patterns is recorded at the distal end of a MMF, forming a measurement matrix during a calibration stage.…”
Section: Introductionmentioning
confidence: 99%
“…By calculating the correct series of input fields, this focused beam can be scanned over an object with a field of view defined by the numerical aperture of the fiber. The second class of methods consists of speckle imaging approaches [14][15][16][17] . With these methods, a set of speckle patterns is recorded at the distal end of a MMF, forming a measurement matrix during a calibration stage.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Recently, more compressive sensing MMF imaging schemes were proposed toward robustness of light transport or fast imaging speed. [27][28][29][30][31][32] On the other hand, it has been widely recognized that reflected light transmitted back through the fiber is beneficial to detect fiber deformation and is promising for imaging without distal access, [33][34][35][36][37] which is critical for practical MMF imaging. One early attempt was by using a virtual coherent point light source placed at the distal fiber tip to dynamically compensate for bending, and the light was focused through a semi-flexible MMF for which the number of conformation is limited.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] Recently, more compressive sensing MMF imaging schemes were proposed toward robustness of light transport or fast imaging speed. [ 27–32 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recent research reported a speckle imaging method based on compressive sensing (CSSI), without complex wave-front shaping, the CSSI method can realize image transmission and reconstruction through a multimode fiber. [10,11,[24][25][26] However, with the limitation of sampling number, calculation time (each imaging process needs independent calculation), and pre-calibration (at the beginning of each experiment), the imaging speed of the CSSI method is difficult to meet the demand of video transmission. Therefore, a method without phase information and pre-calibration that can simulate the nonlinear relationship inside a multimode fiber is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Compared with singlemode fiber with the same external diameter, the core diameter of multimode fiber is dozens of times that of single-mode fiber, which allows multimode fibers to transmit multiple optical modes simultaneously. [8][9][10][11][12] In theory, the hundreds of micronsthick multimode fiber can replace the millimeters-thick fibers DOI: 10.1002/lpor.202200339 bundle used in endoscopes, which can image the tiny spaces that cannot be reached by the existing endoscopes. [13,14] Therefore, multimode fiber is an excellent option to promote the microminiaturization of endoscopes.…”
Section: Introductionmentioning
confidence: 99%